TINJAUAN YURIDIS TERHADAP PENERAPAN KLAUSULA EKSONERASI DALAM PERJANJIAN JUAL BELI BARANG DAN AKIBAT HUKUMNYA - Lisnawati Syamsir (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTThe clause eksoneri In business practice in Indonesia is often found an agreement made outside the provisions of the Code of Civil Code which provisions sayarat called Eksoneri clause or clause penyampingan this often creates a problem because it is very detrimental to the buyer on the intent of the clause umumnya.Adapun eksoneri or penyampingan this clause is to limit the liability of one party, usually the seller, in this case the seller of electronic goods. With eksoneri clause he restricts his responsibility and imposes a duty on the buyer or the words are generally stronger party imposes a duty on the weaker side. The Step - step that must be done in order to be seimbang.Apabila note Eksoneri clause, then the clause in the agreement eksoneri sometimes too one-sided, to the detriment of the other party.